2022
DOI: 10.4314/jasem.v26i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Haematologic tolerance of a rumen fistulation protocol in Udaramsata Tertiary Institution Livestock Teaching and Research Farm, Kaduna State, Nigeria

Abstract: This experiment was conducted at the Federal University Dutsin-Ma Livestock Teaching and Research Farm in Dutsin-Ma Local Government area of Katsina State, Nigeria. The study was aimed at studying haematological tolerance level of Uda rams to a rumen fistulation protocol involving incision of skin and muscles separation along the direction of muscle fibers by divulsion. Blood samples were collected and evaluated at the intervals of 0, 24 and 48hours to assess blood line response to the protocol. A total of 3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Chronic inflammation is characterised by progressive shift in the type of cells present at the site of the inflammation with a rise in simultaneous destruction and healing of the tissue from the inflammatory process (Parakrama et al, 2005). In a study that explored haematologic tolerance of a rumen fistulation regimen in Uda Rams, Jamilu et al (2022) revealed good physiologic tolerance to rumenotomy and fistulation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is characterised by progressive shift in the type of cells present at the site of the inflammation with a rise in simultaneous destruction and healing of the tissue from the inflammatory process (Parakrama et al, 2005). In a study that explored haematologic tolerance of a rumen fistulation regimen in Uda Rams, Jamilu et al (2022) revealed good physiologic tolerance to rumenotomy and fistulation procedures.…”
Section: Introductionmentioning
confidence: 99%